Heart‐specific knockout of the mitochondrial thioredoxin reductase (Txnrd2) induces metabolic and contractile dysfunction in the aging myocardium - Kiermayer, Claudia; Northrup, Emily; Schrewe, Anja; Walch, Axel; de Angelis, Martin Hrabe; Schönsiegel, Frank; Zischka, Hans; Prehn, Cornelia; Adamski, Jerzy; Bekeredjian, Raffi; Ivandic, Boris; Kupatt, Christian; et al. (Journal of the American Heart Association, 2015)
Ubiquitous deletion of thioredoxin reductase 2 (Txnrd2) in mice is embryonically lethal and associated with abnormal heart development, while constitutive, heart‐specific Txnrd2 inactivation leads to dilated cardiomyopathy and perinatal death. The significance of Txnrd2 in aging cardiomyocytes, however, has not yet been examined.
Gesehen am 01.07.2020